Subclinical Myocardial Dysfunction In Patients With Arterial Hypertension With And Without Type 2 Diabetes Mellitus And Diabetic Nephropathy: A Speckle-Tracking Echocardiography Study (Texas Journal of Medical Science, 2026)
Arterial hypertension (HTN) and type 2 diabetes mellitus (T2DM) are major contributors to cardiovascular morbidity and frequently coexist, leading to accelerated myocardial remodeling and heart failure development. Diabetic nephropathy (DN) further aggravates cardiorenal interactions, even in the absence of overt heart failure. Conventional echocardiographic parameters may remain normal during early disease stages, delaying diagnosis of myocardial dysfunction. Objective. To compare subclinical myocardial dysfunction among patients with arterial hypertension alone, arterial hypertension with type 2 diabetes mellitus, and arterial hypertension with type 2 diabetes mellitus complicated by diabetic nephropathy using global longitudinal strain (GLS) and mechanical dispersion (MD). Methods. A total of 120 patients were enrolled and divided into three groups: HTN (n=40), HTN+T2DM (n=40), and HTN+T2DM+DN (n=40). All patients underwent clinical evaluation, laboratory testing, electrocardiography, and transthoracic echocardiography with speckle-tracking analysis. GLS and MD were compared between groups. Results. Left ventricular ejection fraction was preserved in all groups. GLS progressively worsened from HTN to HTN+T2DM and HTN+T2DM+DN groups (−18.9 ± 1.8%, −16.7 ± 2.1%, −14.8 ± 2.4%, respectively; p